Effect of diet and non-esterified fatty acid levels on global transcriptomic profiles in circulating peripheral blood mononuclear cells in early lactation dairy cows - Cheng, Zhangrui; Wylie, Alistair; Ferris, Conrad; Ingvartsen, Klaus; Wathes, D Claire; Consortium, GplusE
After calving, lipid mobilization caused by increased nutrient demands for lactation leads to elevated circulating concentrations of non-esterified fatty acids (NEFA). Excessive NEFA levels have previously been identified as a major risk factor for postpartum immunosuppression. The aim of this study was to investigate changes in global transcriptomic gene expression of peripheral blood mononuclear cells (PBMC) in dairy cows offered different early lactation diets (High, Medium or Low concentrate) and with differing circulating levels of NEFA. Cows were classified as having NEFA concentrations of either 750 µM (High, n=10) at 14 days in milk (DIM). Plasma urea concentrations were greater for cows on the High concentrate diet but β-hydroxybutyrate (BHB) and glucose concentrations did not differ significantly between either dietary treatments or NEFA groups. Cows with High NEFA weighed more at drying off and suffered greater BCS loss after calving. PBMC were isolated at 14 DIM and RNA was extracted for RNA sequencing. Differential gene expression was analysed with DESeq2 with q-value for false discovery rate control followed by Gene Ontology (GO) Enrichment. While there were no differentially expressed genes (DEG) associated with lactation diet, 304 DEG were identified between cows with High and Low circulating NEFA, with 118 upregulated and 186 downregulated. GO enrichment analysis demonstrated that biological adhesion and immune system process were foremost amongst various PBMC functions related to body defences and immunity which were altered. High NEFA concentrations were associated with inhibited cellular adhesion function by down-regulating 20 out of 26 genes (by up to 17 fold) related to this process. Medium NEFA concentrations altered a similar set of functions as High NEFA, but with smaller enrichment scores. Localization and immune system process were most significant, with biological adhesion ranking only eleventh. Our results demonstrated that increased circulating NEFA concentrations but not diet were associated with immune system processes in PBMC in early lactation cows. Leukocyte cell-to-cell adhesion was inhibited when the NEFA concentration exceeded 750 µM, which would reduce the efficiency of diapedesis and so contribute to decreased body defence mechanisms and predispose animals to infection.